Attributes of Public Administration in the System of Law Enforcement under German Administrative Law - A. B. Agapov (Courier of Kutafin Moscow State Law University (MSAL)), 2026)
The fundamental categories of German public law are examined, primarily “public administration” and “law enforcement.” The German administrative-legal doctrine of public administration emphasizes, first and foremost, its basis of authority — the subject of public authority — the Öffentliche Gewalt (public authority) is also the bearer of state authority (Staatsgewalt). Considerable attention is paid to the tenets of public administration, namely, direct state administration (unmittelbare Staatsverwaltung), which always takes into account the federal basis of German statehood, namely, the differences in the powers of the federation and the states with the regional administrative bodies under their jurisdiction. The German administrative-legal doctrine takes into account the status of ordinary subjects of public administration (mittelbare Staatsverwaltung), subordinate to municipal executive bodies. Participants in direct public administration and ordinary subjects are equally endowed with the powers of administrative law subjects (Verwaltungsträger). German General Administrative Law (Allgemeines Verwaltungsrecht) equally considers various organizational and legal forms of administrative law subjects that combine public and private law regulation. These subjects primarily include corporations (associations) (Körperschaften), institutions (Anstalten), and foundations (Stiftungen). The pluralism of administrative law subjects, namely corporations, institutions, and foundations, is determined not only by their public legal purpose and the socially significant goals of their activities, but also — especially in the case of institutions and foundations — by the specific target nature of corporate asset turnover. The binarity of the German federation is considered a fundamental principle of the activities of all its public bodies (Bundesstaatsprinzip), including: and in relation to the delimitation of powers between federal and regional authorities. The three-tiered structure of regional governments is characteristic of most of Germany’s federal states, primarily due to the national and historical characteristics, ethnic, and religious traditions of each of the sixteen states. However, there are also specific differences in the structure of executive bodies in some federal states, particularly Brandenburg, Lower Saxony, Schleswig-Holstein, and Saarland.